Acyl‐Trafficking During Plant Oil Accumulation. Issue 11 (12th October 2015) - Chen, Guanqun; Woodfield, Helen K.; Pan, Xue; Harwood, John L.; Weselake, Randall J.
Abstract: Vegetable oils are an extremely important agricultural commodity. Their use has risen inexorably for the last 50 years and will undoubtedly be even more prevalent in the future. They have a role not only in foodstuffs but also as renewable chemicals. However, our understanding of their metabolism, and particularly its control, is incomplete. In this article we highlight current knowledge and its deficiencies. In particular, we focus on the important role that phosphatidylcholine plays in lipid accumulation and in influencing the quality of the vegetable oils produced.